The potential contribution of end-of-life fishing nets, lines and ropes to a circular economy: the Namibian perspective - Erasmus, Victoria Ndinelago; Johannes, Fillemon Nadhipite; Amutenya, Nangula; James, Neil A. (Frontiers in Sustainability, 2024)
Using data collected through survey questionnaires with fleet managers of 16 (61.5%) Namibian fishing companies, we explored the current practices, challenges, and opportunities in promoting Circular Economy (CE) in the context of End-Of-Life (EOL) fishing gear. Most fishing companies (56.2%) have been in operation for more than 25 years. A majority of fishing companies (62.5%) are involved in demersal trawling, mostly targeting hake (Merluccius species). Survey findings reveal that the companies import fishing gear mostly in a semicomplete format (50.0%). The current durability of fishing nets and lines/ropes is about three and two years respectively, highlighting a continuous generation of fishing gear waste. We estimated (that) approximately 104 tons of EOL fishing gear, lines/twine and ropes (are) generated annually by the Namibian fishing industry, however about 10% of some parts of the EOL fishing gear are recovered and reused. None of the fishing companies recycle EOL fishing gear, which is mostly attributed to a lack of recycling facilities. Current standard practices of EOL fishing nets, lines and ropes management include selling to employees, donating to other institutions, or disposal at dumping sites. Although some of the EOL fishing nets, lines and ropes are sold at open markets, they are not converted into value-added products, thus they are not fully utilised to significantly contribute to the CE. We recommend the implementation of circular practices such as converting EOL fishing nets, lines and ropes into value-added products such as clothing, shoes, and accessories i.e., sunglasses, thereby reducing 2 environmental pollution, minimising energy usage, and promoting sustainable production and consumption.